PENINGKATAN LOYALITAS NASABAH BANK SYARIAH MELALUI PENINGKATAN KUALITAS LAYANAN DAN KEPUASAN NASABAH DENGAN VARIABEL RELIGIUSITAS SEBAGAI VARIABEL MODERATING (Studi pada Bank Syariah di Kota Semarang) - Nurhayati Nurhayati; Fatmasaris Sukesti (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2016)
Competitive rivalry between conventional banks and Islamic banks make Islamic banks should be able to compete with conventional banks in providing good quality of service, product quality and customer satisfaction, thereby increasing the number of customers. Quality of service also can affect customer loyalty directly and indirectly. The quality of service and satisfaction to encourage customers to be loyal to a company's products and services that have an impact on the improvement of market share for a product. Quality of service and customer satisfaction, especially in service companies is very important in retaining customers in a long time. Quality of service and customer satisfaction will determine the performance of the company. Factors religiosity in Indonesia also played in determining and pushing for elections on islamic bank customers because the system for different results offered by the system of interest of conventional banks. These results indicate that the quality of service and level of customer satisfaction and religiosity jointly effect on customer loyalty. Quality of service and customer satisfaction levels also have an effect on customer loyalty which variabels most influence on customer loyalty is the degree of religiosity.